KEBIJAKAN MONETER DAN PENGARUHNYA TERHADAP TINGKAT KEMISKINAN DI LIMA NEGARA ASEAN - Nasution, Lia Nazliana; Sari, Wahyu Indah; Lubis, Andila Br. (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
The purpose of this study is to find leading indicators of poverty rates based on monetary policy in the five ASEAN countries with the highest poverty rates in 2019. This study uses secondary data in the type of panel data, with time-series data starting from 2005 to 2019, and the object of the research country is Indonesia, Laos. PDR, Myanmar, Philippines, and Thailand. Using the ARDL Panel model, the estimation results found interest rates and exchange rates to affect the poverty rate in the long-term in five ASEAN countries, while the exchange rate and the money supply affect in the short term. The leading indicator of poverty levels in the five ASEAN countries from the money supply variable , because t he results are significant in all observed countries except in Lao PDR and Indonesia .